Stress-homogenized spatial architectures via entropy-driven self-assembly enabling high-performance and durable lithium extraction - Xiaoqian Liu; Zewei Hao; Tongcai Liu; Qipeng Zhao; Xuefei Zhou; Yalei Zhang; Huaqiang Chu (Proceedings of the National Academy of Sciences, 2026)
The global transition to sustainable energy demands efficient lithium extraction from brines. While electrochemical lithium extraction using LiMn 2 O 4 (LMO) holds great promise, its practical application is hindered by mechanical degradation caused by anisotropic volume changes and stress accumulation during cycling. Herein, we present an entropy-driven amphiphilic self-assembly strategy that engineers stress-homogenized multilayer core–shell architectures, which innovatively mitigates stress accumulation by tuning the internal geometric structure to optimize stress–strain behavior, thereby synergistically enhancing ion distribution, transport kinetics, and electrochemical stability. This hierarchical interlayer architecture ensures uniform Li + distribution and redistributes internal stresses, mitigating localized stress concentrations and lattice expansion to preserve structural integrity throughout cycling. The optimized LMO establishes a dual benchmark for both capacity and cycling stability in hybrid capacitive deionization, achieving a remarkable lithium extraction capacity of 4.78 mmol g −1 with 96% retention over 100 cycles, outperforming both its unoptimized counterpart and other reported materials of the same type. Finite element simulations further elucidate a 48% reduction in maximum stress compared to disordered counterparts, underscoring the critical coupling between ion diffusion and stress evolution. This paradigm provides a pathway for developing advanced materials with intrinsically stable architectures for sustainable lithium extraction.